2021
DOI: 10.1002/poi3.274
|View full text |Cite
|
Sign up to set email alerts
|

Digital policy in European countries from the perspective of the Digital Economy and Society Index

Abstract: The concept of digital economy has gained currency in recent years and has caught the attention of policymakers and the public. This study uses the 2017 Digital Economy and Society Index indicators—connectivity, human capital, use of Internet services, integration of digital technology, and digital public services—to determine the digital policy performance of various European countries. It uses the co‐plot method to visualize and classify countries based on their correlations with similar variables. The top‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Policy makers and all stakeholders are concerned about the possible developments and opportunities opened up by the digital economy. Digital public policies must foster agility, innovation, and value creation, while the participation of all members of society becomes a priority objective in order to embrace all the opportunities generated by digital progress and innovation, and numerous published reports and research indicate that this is happening every day [69][70][71][72].…”
Section: Discussion and Main Implicationsmentioning
confidence: 99%
“…Policy makers and all stakeholders are concerned about the possible developments and opportunities opened up by the digital economy. Digital public policies must foster agility, innovation, and value creation, while the participation of all members of society becomes a priority objective in order to embrace all the opportunities generated by digital progress and innovation, and numerous published reports and research indicate that this is happening every day [69][70][71][72].…”
Section: Discussion and Main Implicationsmentioning
confidence: 99%
“…Having a reliable device is a central component of digital inclusion, yet many around the globe lack computer access (International Telecommunications Union, 2021;Pew Research Center, 2021b), and even within wealthy countries inequalities persist, leaving many "underconnected" (e.g., Gonzales, 2014Gonzales, , 2016Rideout & Katz, 2016). Much of the discussion about policy solutions to the digital divide has emphasized broadband access (Federal Communication Commission, 2022;King, 2022;United Nations, 2021), and to a lesser degree, efforts to improve digital literacy (e.g., EC, 2021; T. C. Liu, 2022). The purpose of this literature review was to explore policies that inform affordable device access specifically, many of which come from outside the digital divide sector.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in digital skills can be found in countries around the globe. To illustrate the persistent disparities in skills and literacy in wealthy countries, recent assessments found that 43% of Europeans still do not have basic digital skills (T. C. Liu, 2022), and 30% of Americans are considered low in “tech readiness” (McClain et al, 2021). Even in countries that have moved steadily to build technical infrastructure and availability, skills training often lags.…”
Section: The Three Pillars Of Digital Inclusion From a Policy Perspec...mentioning
confidence: 99%
“…Compared with the rapid development of the digital economy, the research on how to measure the development level of the digital economy lags behind. Therefore, academia began to research the index construction and measure the development level of the digital economy (Liu, 2022). , based on the cross-sectional data of eight comprehensive economic zones in China in 2018, evaluated the digital economic level from the aspects of digital infrastructure, digital industry development, and digital application, and found that the development level of the digital economy in China was low.…”
Section: Literature Reviewmentioning
confidence: 99%